BIOLOGY OF WINDOWPANE OYSTER PLACENTA PLACENTA (LINNAEUS) IN KAKINADA BAY - Narasimham, K A (Indian Journal of Fisheries, 2011)
The windowpane oyster, Placenta placenta, attains an average length of 122 mm in 1 year and 157 mm in 2 years. Spawning is biannual, in February- April and October-December, with minor variations. The oyster may spawn more than once during the same spawning season. Majority of the oysters mature for the first time at 53 mm length. The condition index (% meat wt. in total wt.) varies from 8.7 to 18.7 and is higher prior to or at the beginning of spawning and declines with the completion of spawning. The condition index is slightly lower in the oysters infested by pea crab Pinnotheres placunae.